2013
DOI: 10.1021/jo402217e
|View full text |Cite
|
Sign up to set email alerts
|

Converting Cycloalkanones intoN-Heterocycles: Formal Synthesis of (−)-Gephyrotoxin 287C

Abstract: The photochemical rearrangement of N-activated lactams enables their ring contraction concomitant with the migration of a carbon onto a nitrogen atom. When coupled with the Beckmann rearrangement, this photochemical ring contraction converts cycloalkanones into N-heterocycles in a few steps and in a stereospecific manner. To showcase the method, we performed an efficient formal synthesis of (-)-gephyrotoxin 287C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The singlet states minimize to highly strained, protonated, unsaturated lactams. In contrast, Lesard et al ,, demonstrated alkyl migrations resulting in synthetically useful ring contractions of N -chlorolactams and related derivatives (i.e., potential nitrenium ion precursors). An example of these is provided in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…The singlet states minimize to highly strained, protonated, unsaturated lactams. In contrast, Lesard et al ,, demonstrated alkyl migrations resulting in synthetically useful ring contractions of N -chlorolactams and related derivatives (i.e., potential nitrenium ion precursors). An example of these is provided in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…The structure of gephyrotoxin 287C ( 160 ), which possesses a perhydropyrroloquinoline core and five stereocenters, in combination with its neurological profile and low abundance (15 mg from 3200 frogs) has prompted completion of five total syntheses and seven formal syntheses, which intercept various intermediates in Kishi’s synthesis. The discussion below will focus on the total syntheses, but some time will be given to the key steps of the formal syntheses.…”
Section: Synthesesmentioning
confidence: 99%
“…The most recent formal synthesis of gephyrotoxin 287C ( 160 ) was published by the group of Claude Spino of Sherbrooke University in 2013 . Spino’s route featured a Beckmann ring expansion/photochemical ring- ontraction sequence to form the pyrrolidine ring from a cyclopentanone starting material and required 13 steps to reach (−)- 165 , an intermediate in Kishi’s synthesis (Scheme ), in 1.1% yield.…”
Section: Synthesesmentioning
confidence: 99%
“…The acetylative desymmetrisation of a structurally related diol, 69 (Scheme 10), employing a commercial lipase from Pseudomonas uorescens, was used to access the tricyclic enaminone (À)-72, a known intermediate 61 in the synthesis of the poison frog alkaloid (À)-gephyrotoxin. 62 The biotransformation furnished the (2R,5S)-enantiomer of monoacetate 70 in 48% yield and 88% ee, indicating that compared to 67 the increased distance of the reactive atom from the meso "core" of the molecule did not only lead to lower selectivity but also to a switch in the recognised enantiotopic group. From (2R,5S)-70, the target enaminone was obtained in a straightforward sequence comprised of Swern oxidation of the free alcohol, a proline-catalysed, reductive Knoevenagel condensation, and two deprotection steps.…”
Section: Desymmetrisation Of Alcohols and Anhydridesmentioning
confidence: 98%